Recent research on hormonal factors relevant to human aggressiveness. - Hamburg, David A. (International Social Science Journal, 1971)
This article presents findings of a recent research on hormonal factors relevant to human aggressiveness. Hormonal influences upon brain organization early in life have been shown to affect later aggressive and sexual behaviour. However, two highly localized regions of the brain, in the anterior hypothalamus and in the amygdala, have been detected in which this reduction of incorporation of tritiated uridine under testosterone treatment does not occur. These two regions of the brain are implicated by much experimental work in CNS functions related to sexual behaviour and gonodatropin release. Their unique activity in Claytons experiments suggests that they are directly involved in the sexual differentiation process, i.e. testosterone seems to stimulate RNA metabolism only in these two regions of the brain during the critical period for behavioural sex differentiation. Male's early aggressive inclination is developed through social learning and ultimately put to adaptively significant use.